How Work-Life Balance and Perceived Organizational Support Shape Nurse’ Performance Through Job Satisfaction - Ndraha, Julius Ardianto Victorius; Rofiaty; Aryati, Ana Sofia (Profit: Jurnal Adminsitrasi Bisnis, 2026)
Employee performance in healthcare organizations is influenced by organizational conditions and individuals’ responses to work. Nurses, as frontline healthcare workers, face high job demands, requiring a balance between work and personal life and organizational support. This study aimed to analyze the influence of work-life balance and perceived organizational support on nurse performance, with job satisfaction as a mediating variable. This study used a quantitative approach with data collected from nurses in a general hospital. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that work-life balance significantly influenced nurse performance and indirectly through job satisfaction. Perceived organizational support did not directly influence performance but increased job satisfaction, which ultimately influenced employee performance, indicating full mediation. These results confirm that job satisfaction plays a significant role as a mediator connecting work-life balance and perceived organizational support in improving employee performance.